Cretney's principles of family law - Masson, Judith; Bailey-Harris, Rebecca; Probert, Rebecca ([S.l.] : Sweet & Maxwell, 2008)
The fifth edition of this work on family law includes extensive rewriting of the section on child law to reflect the changes of the Children Act 1989. This book is designed to be used by all those involved in the practice of family law and by students and teachers of the subject.
Keywords: Domestic relations; England; Great Britain; Wales